METHODOLOGICAL ISSUES OF COMPREHENSIVE RISK ASSESSMENT FOR RUSSIAN PUBLIC-PRIVATE PARTNERSHIP PROJECTS IN UTILITY SECTOR - S. Repetyuk; E. Tregubova (Вестник университета, 2018)
The relevance of the topic depends on the lack of an integrated approach to assessment of investment risk in infrastructure of Russian public utilities. The authors have developed the proposals for methodology of comprehensive risk assessment for public utilities` investment. This methodology helps to define the organization of this activity. The proposed methodology has developed taking into consideration the logical framework and temporary structure of risk assessment activities for investment projects in Russia’s utility sector and the features ofthese projects. The study determines the composition of activities in the area of comprehensive risk assessment for public utilities` investment, suggested the distribution of responsibilities between the core actors of this work. It also describes means and the methods of comprehensive risk assessment for public utilities` investment, its desired results.